Multiple hosts, multiple impacts: the role of vertebrate host diversity in shaping mosquito life history and pathogen transmission - Vantaux, Amélie; Moiroux, Nicolas; Dabiré, Kounbobr Roch; Cohuet, Anna; Lefèvre, Thierry (Peer Community Journal)

(untitled)
The transmission of malaria parasites from mosquito to human is largely determined by the dietary specialization of Anopheles mosquitoes to feed on humans. Few studies have explored the impact of blood meal sources on the fitness of both the parasite and the mosquito. Our study investigated the effects of 3-4 consecutive blood meals from one of four vertebrate species (human, cattle, sheep, or chicken) on several fitness traits, including mosquito feeding rate, blood meal size, susceptibility to wild isolates of Plasmodium falciparum, survival, fecundity, F1 offspring development time, and size. Our findings revealed no significant effect on parasite development. Similarly, parasite exposure had no overall effects on mosquito fitness. However, blood meal type did have a strong impact on mosquito feeding rate, survival, lifetime fecundity, and offspring size. Specifically, mosquitoes that were fed successive chicken blood meals produced fewer eggs and fewer and smaller F1 adults compared to those fed human blood. Combining our results in a theoretical model, we show a decrease in the vectorial capacity of mosquitoes fed chicken or cow blood and an increase in the capacity of those fed sheep blood compared to those fed human blood. These findings emphasize the importance of considering the diversity of blood meal sources in understanding mosquito ecology and their role in the transmission intensity of malaria parasites.